Community Pharmacists’ Contributions to Disease Management During the COVID-19 Pandemic - Strand, Mark A. (Prev Chronic Dis, 2020)
Community pharmacists assist patients to manage disease and prevent complications. Despite the enormous challenge the coronavirus disease 2019 (COVID-19) pandemic has dealt to the health care system, community pharmacists have maintained the delivery of critical health services to communities, including those most at risk for COVID-19. Community pharmacists are in a key position to deliver priority pandemic responses including point-of-care testing for chronic disease management, vaccinations, and COVID-19 testing.